089 Readiness for the future: young person experience and life skills pilot project. (December 2018) - Parish, E; Hothi, D; Carter, C; Childs, L
Abstract : Background: There are over 4500 young people between the ages of 16–24 at GOSH transitioning to adult services. Young people with long-term conditions often miss out on opportunities to develop skills to aid their readiness for future work due to missed days in education while receiving treatment. In response, GOSH and Morgan Stanley devised a series of life skills days. Project summary: During June-July 2017 we ran a pilot scheme at the London Morgan Stanley offices. The half-day sessions included a networking icebreaker, CV writing exercise, mock interviews and Q and A with staff. Those attending were encouraged to come independently without parents. In case of any medical needs, attendees were accompanied by clinical staff from GOSH. Briefing documents about the experience of young people attending were shared in advance. Results: 3 events were held over a 2 month period. 28 young people attended (aged 15–24 years). All attendees agreed the day was useful to them and all said they would recommend it to others. Attendees rated the experience an average of 9.5 out of 10. The most popular sessions were interview practice and CV writing. Qualitative data was collected on the day. Most young people attending lived in, or close to, London but some young people travelled considerable distances to attend (Newcastle, St Albans, Buckinghamshire, Essex). Discussion: Part of the continuous care of young people is supporting their development to fulfil their potential. Young people enjoyed the events and some have benefitted from subsequent mentoring and work experience. We are conscious that travel costs could prove to be prohibitive, especially for those outside London, and are working with GOSH Charity to improve the accessibility and sustainability of the model. We are in the process of co-creating future events with the Young People's Forum.